Analysis of the Development Needs for Interactive Web-Based E-book on Pressure Topic for Differentiated Science Learning - Ariastya , Ribkah Melia; Astuti, Indri; Enawaty, Eny (Department of Physics Education, Universitas Mataram, 2023)
This research aims to describe the needs analysis results conducted at SMP Negeri 19 Singkawang as the basis for developing web-based interactive e-book teaching materials on pressure for differentiated science learning. This study is a Research and Development study. The researcher employed a qualitative descriptive research method. Data collection techniques included non-test instruments such as questionnaires, interviews, observations, and documentation. Data analysis was conducted using a qualitative approach. The development of web-based interactive e-books utilized the 4D development model, consisting of four stages: define, design, develop, and disseminate. This study served as a preliminary study in the define stage, where the researcher ensured that the developed product would meet the needs of teachers and students. Based on the findings, students highly demanded web-based interactive e-book media for the topic of pressure. The researcher concluded that students require engaging, interactive teaching materials that can be easily accessed through their frequently used smartphones and contain diverse content with various media formats that cater to their learning styles. Teachers require interactive e-books to enhance the quality of science teaching on the topic of pressure. Differentiated science learning strategies integrated into interactive e-book are necessary for teachers to provide appropriate teaching materials and media that meet the student's learning needs. The availability of supporting facilities and adequate internet connection allows the utilization of web-based interactive e-books on the topic of pressure by students at SMP Negeri 19 Singkawang.